Reconstructing Professional Zakat: A Payment Model for Gig Economy Workers in Surabaya - Najah ahmadun; Basar Dikuraisyin (Journal of Management and Business Innovations, 2025)
The development of the gig economy has transformed income streams into irregular, project-based arrangements, posing new challenges for the concept of calculating professional zakat. Meanwhile, discussions on fiqh and zakat legislation remain focused on fixed income structures. This creates a conceptual gap in the application of professional zakat in the gig economy ecosystem. This study aims to formulate a new concept in the professional zakat calculation model in the context of the gig economy, focusing on digital market platform workers such as influencers and TikTokers in Surabaya with a sample of three influencers and two TikTokers. This study uses a qualitative phenomenological approach, collecting data through in-depth interviews. The results show that zakat in the gig economy is calculated based on real-time income flows rather than annual accumulations. This model reflects contextual justice and spiritual accountability, in accordance with the principles of maqasid sharia. This research contributes a new zakat calculation model that is suitable for contemporary gig-based livelihoods, which is ultimately unique because it offers theoretical refinement and practical guidance for modern zakat governance. Keyword: Gig Economy, Profesional Zakat, Zakat Payment